Green Hydrogen Production Technologies from Ammonia Cracking - Hossein Ali Yousefi Rizi; Donghoon Shin (Energies, 2022)
The rising technology of green hydrogen supply systems is expected to be on the horizon. Hydrogen is a clean and renewable energy source with the highest energy content by weight among the fuels and contains about six times more energy than ammonia. Meanwhile, ammonia is the most popular substance as a green hydrogen carrier because it does not carry carbon, and the total hydrogen content of ammonia is higher than other fuels and is thus suitable to convert to hydrogen. There are several pathways for hydrogen production. The considered aspects herein include hydrogen production technologies, pathways based on the raw material and energy sources, and different scales. Hydrogen can be produced from ammonia through several technologies, such as electrochemical, photocatalytic and thermochemical processes, that can be used at production plants and fueling stations, taking into consideration the conversion efficiency, reactors, catalysts and their related economics. The commercial process is conducted by using expensive Ru catalysts in the ammonia converting process but is considered to be replaced by other materials such as Ni, Co, La, and other perovskite catalysts, which have high commercial potential with equivalent activity for extracting hydrogen from ammonia. For successful engraftment of ammonia to hydrogen technology into industry, integration with green technologies and economic methods, as well as safety aspects, should be carried out.